1996
DOI: 10.1093/ajcp/105.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Antigen, CD13, CD14, and/or CD33 Expression Is Restricted to Certain Lymphoid Neoplasms

Abstract: The authors examined the expression of myeloid antigens (MyAg): CDMb, CDI3, CD14, CD15, and CD33 in 249 adults with lymphoid neoplasms using flow cytometric analysis. In this study, acute leukemia that was myeloperoxidase negative by light microscopy and had at least one lymphoid antigen was defined as acute lymphoblastic leukemia (ALL). The patients were classified as follows: 6 with unclassified ALL, 35 early B precursor ALL, 32 T-ALL, 25 B-cell chronic lymphocytic leukemia (B-CLL) and its variants, 24 B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…Studies have also shown that CD13 and CD33 positivity is commonly seen in 6-16% and 3-10% of ALL cases respectively [36][37][38] and they are frequently associated with t(9;22). 39,40 In our study, we found Philadelphia chromosome t According to available literature, CD7 expression is seen in 20% of AML, CD19 in 5% of AML, CD10 in 3% of AML, and sCD3 in 1% of AML. [41][42][43] This was in close concordance with our study results.…”
Section: Comparison Of Other Markers Used In the Two Panelssupporting
confidence: 55%
“…Studies have also shown that CD13 and CD33 positivity is commonly seen in 6-16% and 3-10% of ALL cases respectively [36][37][38] and they are frequently associated with t(9;22). 39,40 In our study, we found Philadelphia chromosome t According to available literature, CD7 expression is seen in 20% of AML, CD19 in 5% of AML, CD10 in 3% of AML, and sCD3 in 1% of AML. [41][42][43] This was in close concordance with our study results.…”
Section: Comparison Of Other Markers Used In the Two Panelssupporting
confidence: 55%
“…Although it has been reported infrequently in many different subtypes of mature lymphoid neoplasm, aberrant myeloid antigen expression is perhaps most often found in lymphoplasmacytic lymphoma (LPL). 16 Notably, CD5 expression on B cells is often referred to as an aberrant phenotype, but small populations of normal, mature CD5 ϩ B cells exist. Nonneoplastic CD5 ϩ B cells are found most often in the peripheral blood, but may also be seen in lymph node specimens, especially in patients with autoimmune disease.…”
Section: Identification Of Abnormal Mature B-lymphoid Cellsmentioning
confidence: 99%
“…However, this was concluded only from experiments using resialylated red blood cells (11). Siglec-3 is found on myelomonocytic progenitor cells, monocytes, and macrophages and is a marker for acute myeloid leukemias (31)(32)(33), but no specific function has yet been ascribed to it. Siglec-4a (myelin-associated glycoprotein) is found only in the nervous system and is involved in maintenance of myelin sheath integrity (34,35).…”
mentioning
confidence: 99%